Review of the Potential of Kamandrah (Croton Tiglium L.) As A Medicinal Plant - Kurniasari, Fitri; Widyasti, Jena Hayu (Asian Journal of Pharmaceutical Research and Development, 2023)
Herbal plants are widely used to cure various diseases. Research from the Euphorbiaceae family shows activity against cancer and tumors. Croton is a member of the Euphorbiaceae family which has wide uses in the field of medicine. The Croton genus consists of various species including Croton lechleri, Croton palanostigma, Croton dracoides, and Croton tiglium with various useful secondary metabolite contents. The plant Croton tiglium L is a medicinal plant originating from China, South Asia, and India. The seeds, leaves, bark and roots of C.tiglium can relieve various diseases, including: antifungal, anti-inflammatory, anticonvulsant, wound healing, antitumor activity. The main compound content of Croton tiglium is alkaloids, flavonoids and diterpenes. The literature review aims to explore C tiglium plants based on morphological characteristics, therapeutic uses, pharmacological actions and activities and plant compound content. The research method used was to collect and analyze the selected literature electronically with the keywords "Croton tiglium L", "Chemical constituent", "isolation", "Pharmacological action", and "Therapeutic use". Selected literature included international and national journals that had been published on several sites, such as NCBI, Elsevier, and Pubmed, and others. Selected literature in the form of journals consisting evidence and information on chemical content and pharmacological activity.